PO242 Factors influencing adherence to tibial nerve stimulation for the management of neurogenic overactive bladder. (1st December 2017) - Salatzki, Janek; Spanudakis, Eleanora; Gonzales, Gwen; Vinas, Gregoria; Baldwin, Joanne; Haslam, Collette; Liechti, Martina; Panicker, Jalesh N
Abstract : Introduction: Bladder dysfunction is common following neurological disease and Percutaneous Tibial Nerve Stimulation (PTNS) is an established minimally-invasive outpatient treatment for managing neurogenic overactive bladder symptoms (OAB). Following a 10–12 week treatment (once-weekly), responders return for top-up treatments (top-ups) when OAB recurs. This study aims to evaluate factors influencing patients's decision to return for top-ups. Methods: Patients with neurogenic OAB attending 12 week PTNS were prospectively evaluated using standardised bladder questionnaires (ICIQ-OAB, ICIQ-LUTSqol), three-day bladder diary and satisfaction questionnaire. Responders to PTNS were invited to return for top-ups and divided into returning for top-ups (group-1) and not returning (group-2). PTNS service evaluation questionnaire (PTNS-SEQ) retrospectively enquired about treatment effects, side-effects, and procedural/logistical difficulties. Results: 73 patients completed PTNS-SEQ (non-responders (n=25), responders returning group-1 (n=31) and not returning for top-ups group-2 (n=17)). Age, gender, and neurological diagnosis were comparable across groups. Responders experienced significant improvement in OAB (group-1:−1.85±2.28, p<0.001; group-2:−1.54±1.85, p<0.05) and quality of life (group-1:−5.35±6.90, p<0.001; group-2:−4.27±10.98, p>0.05) following treatment. Group-1 experienced a greater improvement compared to group-2 in 24 hour urinary frequency (p<0.01), number and severity of incontinence episodes (p<0.01). In the PTNS-SEQ, differences between group-1 and −2 were satisfaction with the Service and lack of treatment effect (p<0.05). Conclusion: Improvements in 24 hour urinary frequency and severity of incontinence impact patients´s satisfaction with PTNS service and their decision to return for top-ups.